Effects of Target Size and Test Distance on Stereoacuity - Yo Iwata; Fusako Fujimura; Tomoya Handa; Nobuyuki Shoji; Hitoshi Ishikawa (Journal of Ophthalmology)
Target size and test distance effects on stereoacuity were investigated in 24 subjects using a three-dimensional monitor. Examination 1: Target Size Effects. The test distance was 2.5 m for 0.1°, 0.2°, 0.5°, and 0.9° target sizes; crossed parallax was presented in 22-second units. Average stereoacuity values for 0.1°, 0.2°, 0.5°, and 0.9° target sizes were 59.58±14.86, 47.66±13.71, 41.25±15.95, and 39.41±15.52 seconds, respectively. Stereoacuity was significantly worse with a 0.1° target than with 0.2°, 0.5°, and 0.9° target sizes (P=0.03, P<0.0001, and P<0.0001, resp.). Examination 2: Test Distance Effects. Test distances of 2.5, 5.0, and 7.5 m were investigated for a 0.5° target size; crossed parallax was presented in 22-second units. Average stereoacuity values at 2.5 m, 5.0 m, and 7.5 m test distances were 44.91±16.16, 34.83±10.84, and 24.75±7.27 seconds, respectively. Stereoacuity at a 7.5 m distance was significantly better than at distances of 2.5 m and 5.0 m (P<0.0001 and P=0.02, resp.). Stereoacuity at a 5.0 m distance was significantly better than at 2.5 m (P=0.04). Stereoacuity should be estimated by both parallax and other elements, including test distance and target size.